A New Concept in Public Relations: A Systematic Review on "Corporate Social Advocacy" - Aycan Ulusan; Beris Artan Özoran (Akademik İncelemeler Dergisi)
The increasing public demand for brands to contribute to the creation of a ‘more livable world’ has played a critical role in shaping the transformation of corporate strategies centered around corporate social advocacy. This shift has also necessitated further academic inquiry into the subject. In this context, this study aims to offer both a conceptual evaluation of corporate social advocacy and a systematic review of academic research conducted in this field. The findings suggest that corporate social advocacy is gaining substantial prominence in both corporate and academic contexts. However, the review also identifies notable methodological gaps within the existing body of literature. Furthermore, an important observation is that the majority of studies focus predominantly on U.S. corporations and societal issues, leading to a body of literature that is largely constrained to the U.S. context.